1998
DOI: 10.1093/ajcn/67.6.1162
|View full text |Cite
|
Sign up to set email alerts
|

Energy expenditure, physical activity, and body composition of ambulatory adults with hereditary neuromuscular disease

Abstract: Persons with neuromuscular disease (NMD) have progressive weakness and wasting of skeletal muscle, reduced fat-free mass, and increased fat mass relative to healthy control subjects. To test the hypothesis that resting energy expenditure (REE), estimated total daily energy expenditure (TEE), and physical activity patterns are altered in ambulatory adults with NMD, 26 adult men and women with slowly progressive NMD and 19 able-bodied control subjects similar in age and weight were evaluated. REE was measured af… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
33
1
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(39 citation statements)
references
References 25 publications
4
33
1
1
Order By: Relevance
“…Flex heart rate has been used in a previous study. 8 The results of our study, with flex heart rate being greater in neuromuscular disease participants, were consistent with that study. The definition of a reproducible flex heart rate to distinguish between resting and activity heart rate is problematic as it is based on the assumption that one discrete pulse point can provide a clear-cut physiological distinction between rest and exercise.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Flex heart rate has been used in a previous study. 8 The results of our study, with flex heart rate being greater in neuromuscular disease participants, were consistent with that study. The definition of a reproducible flex heart rate to distinguish between resting and activity heart rate is problematic as it is based on the assumption that one discrete pulse point can provide a clear-cut physiological distinction between rest and exercise.…”
Section: Discussionsupporting
confidence: 92%
“…Participants with neuromuscular disease walked at 1.6, 2.5 and 3.2 km/h or 1.1, 1.8 and 2.4 km/h according to ability. This is consistent with a previous study, 8 allowing comparisons to be made. Heart rate was recorded and stored at 15-second intervals.…”
Section: Minutes Activesupporting
confidence: 92%
“…Low cardiorespiratory fitness was also found in 50% of the persons who performed the submaximal cycle ergometer test. Although the issue is sparsely studied, several authors have noted that persons with slowly progressive neuromuscular diseases such as DM1 risk developing secondary chronic conditions such as cardiovascular diseases and diabetes, due to reduced physical activity, a sedentary lifestyle and obesity [45,46]. Features of the metabolic syndrome, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…In adult patients with various types of neuromuscular disease, including some DMD patients, MCCRORY et al [26] found a preserved REE but a reduced total daily energy expenditure. In patients with myotonic dystrophy, JOSEFOWICZ et al [24] reported a reduction in REE expressed as a function of body surface area, but an augmentation when expressed as a function of FFM.…”
Section: Energy Expenditure and Neuromuscular Diseasesmentioning
confidence: 99%
“…Patients in the current study, however, were adults, had a dramatically reduced muscle mass and had patent chronic respiratory insufficiency. In the studies of MCCRORY et al [26], HANKARD et al [27], and ZANARDI et al [28], the patients were not mechanically ventilated and had a relatively preserved FFM. In this regard, it is important to keep in mind the data provided by ZURLO et al [29], showing that skeletal muscle can account for up to 20% of REE, and the data of KAYSER [30] showing that skeletal muscle is responsible for 25% of V9O 2 of the body.…”
Section: Energy Expenditure and Neuromuscular Diseasesmentioning
confidence: 99%